From imaging techniques to laboratory tests: a multimodal stratification for varicocele-associated decreased semen quality - Anmin Wang; Hongyuan Chang; Dicheng Luo; Hao Wang; Hui Lv; Wenxiao Yu; Fu Wang (Basic and Clinical Andrology)
Abstract Background Varicocele adversely affects male fertility by impairing semen quality, yet there remains no unified approach that combines advanced imaging and laboratory markers for clinical stratification. To develop a uniform clinical stratification system, we conducted a review of the literature across major databases. Results Shear wave elastography thresholds above 5.235 kPa and spermatic vein diameters exceeding 2.5 mm on color Doppler ultrasound demonstrated strong, independent correlations with decreased sperm concentration, motility, and morphology. Among laboratory tests, elevated follicle-stimulating hormone, low inhibin B, and others were consistently linked to poorer semen quality. Biomarkers such as cysteine-rich secretory protein 3 showed potential. Conclusions We propose a multimodal stratification framework integrating evidence‑based cutoffs for shear wave elastography and color Doppler ultrasound with key laboratory indices. Adoption of standardized protocols and consensus guidelines will facilitate personalized diagnosis, improve prognostic accuracy, and guide management of varicocele‑decreased semen quality.